THE DEVELOPMENT OF THE AFRICAN UNION - Erunke Canice Esidene; Uchem Raphael Onyebuchi (European Scientific Journal, ESJ, 2012)
The problem of socio-economic development, political stability and social cohesion in the African sub-region has necessitated the paradigm shift from the old order of doing things to a more dynamic approach aimed at correcting the wrongs bedeviling the black race. Africa, generally known as the „dark continent‟ by most scholars with western orientation has suffered a plethora of social vises including high rate of poverty, crime, corruption in both low and high places; economic downturn, brain drain, political instability, armed robbery, indiscipline ,high rate of maternal and child mortality, child labour and human trafficking, to mention but a few. These problems as they are, have literally defied all acceptable solutions over time. Of particular importance is the issue of enhancing peace, stability and tranquility in the region going by the spate of war, violation of human fundamental rights, criminality, terrorism, threats of secession, etc. Thus, with the invention and/or formation of the Organization of African Unity in 1963 and the subsequent transformation of the nomenclature to African Union in 2001, the African quagmire appears to be the same in both content and character. The paper is a theoretical explanation of the situation at stake aimed at bringing about a viable resolution to African socio-economic and political malaise devoid of personal or elite interests. The paper adopts analytical framework through relevant existing literatures by way of content analysis. The study sums up with policy recommendations for overall stability, progress and development of the African sub-region in its entirety in the 21st century and beyond.